DNA diversity in olive (Olea europaea L.) and its relationships with fatty acid, biophenol and sensory profiles of extra virgin olive oils. (August 2016) - Grasso, Filomena; Paduano, Antonello; Corrado, Giandomenico; Ambrosino, Maria Luisa; Rao, Rosa; Sacchi, Raffaele
Abstract: Olive ( Olea europaea L.) is gaining importance worldwide primarily for the production of virgin olive oil (VOO), the main lipid source of the Mediterranean diet. We evaluated the genetic diversity of 20 traditional varieties of Southern Italy using 10 SSR markers. We also produced 382 monovarietal extra virgin olive oils (EVOOs) from the same varieties and studied their chemical profiles by analysing 13 fatty acids (FAs) and 6 olive biophenols (OBPs). In addition, the sensory profile of EVOOs was also assessed. Significant differences among the 20 varieties were found in terms of DNA polymorphism, chemical composition and sensory profile of the EVOOs, highlighting that the genetic variability in olive is detected also in different EVOO features. The chemical variation of EVOOs throughout different years suggested a genotype-specific level of environmental stability and adaptation. The comparison of pairwise distances between varieties obtained by genetic, chemical and sensory data indicated a significant correlation of sensory attributes with the other parameters. The genetic and EVOO composition data underlined the significant diversity present in the varieties under investigation, suggesting that traditional varieties specialized to particular environmental conditions have distinctive, unexplored features. Our work also shows the efficacy of establishing integrated compositional databases as a means to make evident differences among VOOs from traditional varieties. This multidisciplinary information is highly useful to differentiate origin-linked products from others of the same category. Graphical abstract: Highlights: Ten SSRs were used to fingerprint twenty olive cultivars of Southern Italy. Thirteen fatty acids, six olive biophenols and sensory profile were determined in their EVOOs. Varieties significantly differed for their DNA polymorphism, EVOO composition and sensory profile. Distances in sensory data correlated with those of other measured parameters. The genetic variability in olive is evident also in the biochemical and sensory attributes of EVOOs.